Positron Emission Tomography Imaging of Acinetobacter baumannii Infection: Comparison of Gallium-68 Labeled Siderophores - Dvorakova Bendova, Katerina; Krasulova, Kristyna; Neuzilova, Barbora; Popper, Miroslav; Mlynarcik, Patrik; Hajduova, Katarina; Novy, Zbynek; Hajduch, Marian; Petrik, Milos (ACS infectious diseases, 2025)
Acinetobacter baumannii (AB) is an opportunistic pathogen with growing clinical relevance due to its increasing level of antimicrobial resistance in the last few decades. In the event of an AB hospital outbreak, fast detection and localization of the pathogen is crucial, to prevent its further spread. However, contemporary diagnostic tools do not always meet the requirements for rapid and accurate diagnosis. For this reason, we report here the possibility of using gallium-68 labeled siderophores, bacterial iron chelators, for positron emission tomography imaging of AB infections. In our study, we radiolabeled several siderophores and tested their in vitro uptake in AB cultures. Based on the results and the in vitro properties of studied siderophores, we selected two of them for further in vivo testing in infectious models. Both selected siderophores, ferrioxamine E and ferrirubin, showed promising in vitro characteristics. In vivo, we observed rapid pharmacokinetics and no excessive accumulation in organs other than the excretory organs in normal mice. We demonstrated that the radiolabeled siderophores accumulate in AB-infected tissue in three animal models: a murine model of myositis, a murine model of dorsal wound infection and a rat model of pneumonia. These results suggest that both siderophores radiolabeled with Ga-68 could be used for PET imaging of AB infection.
Keywords: radioizotopy galia; siderofory; Acinetobacter Infections; myši; krysa rodu Rattus; Acinetobacter baumannii; infekce bakteriemi rodu Acinetobacter; Animals; Disease Models, Animal; modely nemocí na zvířatech; Mice; zvířata; Rats; Positron-Emission Tomography; Siderophores; Gallium Radioisotopes; pozitronová emisní tomografie